THE THERMODYNAMICS AND PHASE TRANSITION OF ADS/CFT BLACK HOLES - Widianingrum, Nuriawati
AdS/CFT correspondence is a correspondence that involves gravitational theory and gauge theory through a holographic principle. The considered gravitational theory is the black holes in 5-dimensional Anti-de-Sitter spacetime or AdS5 black holes. While, the gauge theory is the conformal field theory, i.e. field theory with conformal invariance SO(2,4), in 4-dimensional spacetime (CFT4). Black holes emit thermal radiation known as Hawking radiation, so that black holes have temperature. Thus, black holes will have thermodynamic properties as thermal systems in general. This research discusses about the correspondence between black holes and the laws of thermodynamics, and calculates the thermodynamic quantities of black holes. Afterwards, the results are applied to calculate the thermodynamic quantities of the AdS5 black hole. Derivation of thermodynamic quantities can be carried out by first deriving the action. The AdS/CFT correspondence provides the equivalence of the partition function of the AdS5 black holes to the partition function of CFT4. After the action is obtained, the thermodynamic quantities of the AdS5 black hole are calculated, and can be interpreted as CFT thermodynamic quantities on the surface of the AdS5 black hole. The black hole's temperature can also fluctuate. As a result, black holes can undergo phase transition. The phase transition that occurs in black holes are classified as first-order phase transitions.